Productivity, preferences and UIP deviations in an open economy business cycle model - Arnab Bhattacharjee; Jagjit S. Chadha; Qi Sun (University of Kent, Department of Economics, 2008)
We show that a flex-price two-sector open economy DSGE model can explain the poor degree of international risk sharing and exchange rate disconnect. We use a suite of model evaluation measures and examine the role of (i) traded and non-traded sectors; (ii) financial market incompleteness; (iii) preference shocks; (iv) deviations from UIP condition for the exchange rates; and (v) creditor status in net foreign assets. We find that there is a good case for both traded and non-traded productivity shocks as well as UIP deviations in explaining the puzzles.
Keywords: E32; F32; F41; 330; current account dynamics; real exchange rates; incomplete markets; financial frictions; Ungleichgewichtiges Wachstum; Offene Volkswirtschaft; Home Bias Puzzle; Produktivität; Konjunktur; Dynamisches Gleichgewicht; OECD-Staaten